2022
DOI: 10.1039/d2nj01301k
|View full text |Cite
|
Sign up to set email alerts
|

Hematite nanoparticles decorated nitrogen-doped reduced graphene oxide/graphitic carbon nitride multifunctional heterostructure photocatalyst towards environmental applications

Abstract: The carcinogenic heavy metals and aromatic organic compounds linger as wastewater pollutants implying great menace to the ecological balance. To solve these environmental pollution problems, the photocatalytic process is an...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 75 publications
1
23
1
Order By: Relevance
“…To examine the potential growth of the GNFC nanocomposite and the progressive deposition of NiFe 2 O 4 and CuS on the surface of SrGO nanosheets, we performed FESEM measurements for GO, NiFe 2 O 4, CuS, GNF, and GNFC-13 (Figure ). It was noticed that the GO synthesized by the modified Hummers process has a transparent wrinkled sheet-like morphology (Figure a). , The FESEM image of NiFe 2 O 4 nanoparticles prepared by the solvothermal route depicted in Figure b demonstrated that the nanoparticles are predominantly spherical and porous in nature, with slight variation in sizes. On the other hand, the as-synthesized CuS was in the shape of highly dense spherical nanoparticles, as depicted in Figure c.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…To examine the potential growth of the GNFC nanocomposite and the progressive deposition of NiFe 2 O 4 and CuS on the surface of SrGO nanosheets, we performed FESEM measurements for GO, NiFe 2 O 4, CuS, GNF, and GNFC-13 (Figure ). It was noticed that the GO synthesized by the modified Hummers process has a transparent wrinkled sheet-like morphology (Figure a). , The FESEM image of NiFe 2 O 4 nanoparticles prepared by the solvothermal route depicted in Figure b demonstrated that the nanoparticles are predominantly spherical and porous in nature, with slight variation in sizes. On the other hand, the as-synthesized CuS was in the shape of highly dense spherical nanoparticles, as depicted in Figure c.…”
Section: Resultsmentioning
confidence: 94%
“…06-0464) . The XRD diffraction peak centered at 11.1° indexed as the (001) diffraction plane arising from the GO interlayer spacing . Beyond that, the characteristic peak of GO could not be detected in GNF, GC, and GNFC hybrid nanocomposites suggesting good exfoliation of GO during the solvothermal-reflux process, which was a result of disruption of the GO layer structure caused by the interlayer development of NiFe 2 O 4 and CuS crystals. , As shown in Figure S1, in the NFC nanocomposite both the characteristic diffraction peaks of NiFe 2 O 4 and CuS were observed, indicating the successful formation of the binary nanocomposite.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations